2004
DOI: 10.1021/bi049667e
|View full text |Cite
|
Sign up to set email alerts
|

Role of Disulfide Bonds for the Structure and Folding of Proguanylin

Abstract: The intestinal peptide hormone guanylin circulates mainly as its corresponding prohormone of 94 amino acids and is the first identified endogenous ligand of intestinal guanylyl cyclase C. While the prohormone is biologically inactive, it is processed to the fully functional form with 15 amino acid residues corresponding to the COOH terminus of the precursor protein. In addition to this inactivation of the hormone region, the prosequence makes an essential contribution to the disulfide-coupled folding of the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In biology, the disulfide bond is an important part of the secondary and tertiary structures of proteins, which is formed between the mercapto groups of cysteine residues 4,5 . It plays an important role in the formation of the three‐dimensional structure of protein molecules 6,7 . Cleavage under the action reducing agents is one of the most important properties of disulfide bonds 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…In biology, the disulfide bond is an important part of the secondary and tertiary structures of proteins, which is formed between the mercapto groups of cysteine residues 4,5 . It plays an important role in the formation of the three‐dimensional structure of protein molecules 6,7 . Cleavage under the action reducing agents is one of the most important properties of disulfide bonds 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…The existing experimental evidence on the oxidative folding of guanylin 67 and proguanylin 74 , 76 , 77 provides a good insight into the role of the prohormone. As it appears, the body of proguanylin folds first; the folded body provides a template for subsequent oxidative folding of the guanylin tail.…”
Section: Resultsmentioning
confidence: 99%
“…This effect has sometimes been termed intramolecular chaperoning (62)(63)(64)(65). Recently, Lauber et al reported the structural study of the proguanylin and several mutants and showed that the N-terminal β-strand of the prosequence makes an essential contribution to the disulfide-coupled folding of the guanylin hormone (66).…”
Section: Discussionmentioning
confidence: 99%